(untitled) (Ustozlar uchun, 2026)
The rise of social media has transformed the landscape of communication, introducing new linguistic forms such as memes, slang, and rapidly evolving expressions that challenge traditional approaches to translation. This article examines how these dynamic and highly contextualized forms of language complicate the process of cross-cultural communication within the framework of Translation Studies. Unlike conventional texts, social media content is often multimodal, combining text, images, and cultural references that require translators to interpret meaning beyond the verbal level.